Marketing automation unleashed : the strategic path to B2B Growth - Cheshire, Casey, ....- (Charleston : Advantage Media Group, 2020)
The Marketers Manual to All Things AutomatedAt a time when the importance of understanding the world of automated marketing has never been greater, Marketing Automation Unleashed: The Strategic Path to B2B Growth takes readers on an in-depth exploration of marketing automation and its significant impact on how we do business today.Casey Cheshire employs nearly a decade of experience as a marketing leader and consultant, as well as his in-depth discussions with industry experts, to deliver a comprehensive tutorial on the wide array of strategies, techniques, tools, and uses of marketing automation.Cheshire explains in detail how to build a successful marketing automation campaign by following the Cheshire Success Index, a ten-step program divided into four distinct phases: Foundational, Growth, Alignment, and Optimization. Each phase leads readers through a series of questions and strategies to aid them in setting up cutting-edge marketing campaigns that are as effective as they are efficient. Along the way you will discover ways to bridge the all-too-common gap between sales and marketing teams, tools to help you identify and engage your customer, new techniques for nurturing your customer, and how to test the effectiveness of your campaign as it progresses without the tedious headache of traditional methods. Marketing Automation Unleashed: The Strategic Path to B2B Growth is an easy-to-read guide through the changing terrain of the marketing world, one focused on the ultimate goal of generating revenue rather than simply bringing in lead.
Keywords: Marketing ; automation